Re: Caron et al., 2021, sociocultural context and autistics quality of life: A comparison between Quebec and France. (February 2022) - Rodgers, Jacqui
The purpose of this letter to the editors is to highlight to the readership of Autism the recommended use of the Autism Quality of Life measure (ASQoL) for research with autistic adults. The ASQoL was developed for use alongside the World Health Organization Quality of Life – Bref (WHOQOL-Bref) and the World Health Organization disabilities module. The letter raises some concerns about the use of the ASQoL as a standalone measure in a recent study by Caron et al. published in Autism . Lay abstract: This letter to the editors discusses the use of the ASQoL for research with autistic adults. The autism quality of life measure was developed for use alongside two existing measures of quality of life developed by the World Health Organization. It was not developed as a questionnaire to be used in its own. The letter raises some concerns about the use of the autism quality of life measure as a standalone measure in a recent study by Caron et al., published in Autism .